Naproxen: A universal analgesic with a minimal risk of cardiovascular events - A. E. Karateev (Современная ревматология, 2016)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are a main tool used in real clinical practice to relieve acute pain and to control major symptoms in chronic diseases of the joint and spinal column. They are effective and easy-to-use; however, they may cause adverse reactions (ARs) that require careful monitoring and effective prevention. The current concept of the safe use of NSAIDs is aimed at maximally reducing both gastrointestinal and cardiovascular events. Clinical trials and population-based studies have revealed that among all NSAIDs (other than aspirin), naproxen is associated with the least cardiovascular risk. This drug that belongs to traditional (nonselective) NSAIDs (n-NSAIDs) has been commonly used in clinical practice for more than 40 years and gained physicians’ confidence worldwide as a reliable analgesic and anti-inflammatory agent. The therapeutic potential of naproxen has been proven in a great variety of diseases and abnormalities: from acute injuries to Bechterew’s disease. When using naproxen, like other n-NSAIDs, it should be borne in mind that gastrointestinal ARs may develop. However, this risk may be substantially decreased by the administration of proton pump inhibitors, such as pantoprazole. This review presents basic investigations that have studied the efficacy and safety of naproxen.